Study of indoor air quality (IAQ) using one-way Anova - Anuar M.I.S.M.; Mardi N.H.; Zaini N.; Zahari N.M. (American Institute of Physics Inc., 2023)
This study assessed the physical and chemical parameters related to indoor air quality (IAQ) at Universiti Tenaga Nasional (UNITEN) and the IAQ of selected campus buildings were compared with guidelines provided by DOSH. This study is especially important as students spend most of their time indoors thus making them more vulnerable to exposure to indoor contaminants. Seven sampling locations around the UNITEN campus were selected which all have different layout. The method of data collection is based on Industry Code of Practice on Indoor Air Quality 2010 (ICOP). The indoor contaminants were recorded using real-time monitoring method and the parameters of interest are the Particulate Matter (PM2.5 and PM10), Total Volatile Organic Compound (TVOC), relative humidity and temperature. Results show that the parameters of IAQ level in UNITEN is at a safe level as it is well below the DOSH permissible limit. One-way ANOVA analysis was used to identify whether or not the mean of the IAQ parameters specifically PM2.5, PM10 and TVOC are the same and belongs to the same population. Statistical analysis also shows that there was no significant difference in IAQ level between all sampling locations (P?0.05). 2021 Author(s).